2019
DOI: 10.1016/j.aap.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

A new integrated collision risk assessment methodology for autonomous vehicles

Abstract: Real-time risk assessment of autonomous driving at tactical and operational levels is extremely challenging since both contextual and circumferential factors should concurrently be considered. Recent methods have started to simultaneously treat the context of the traffic environment along with vehicle dynamics. In particular, interaction-aware motion models that take inter-vehicle dependencies into account by utilizing the Bayesian interference are employed to mutually control multiple factors. However, commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…The results of their study showed some disbenefit of adopting CAVs in low penetrations (like 20%), whereas a high penetration rate (like 90%) has significantly reduced the conflicts at junctions, which substantially help increase safety. Katrakazas et al (2019) further explore these issues using a SSAM approach and find that this approach could be used in AVs to find dangerous road users and produce manoeuvres for other road users to avoid possible accidents. Table 1 reviews studies with a focus on the simulation of AVs and CAVs and the acquired methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of their study showed some disbenefit of adopting CAVs in low penetrations (like 20%), whereas a high penetration rate (like 90%) has significantly reduced the conflicts at junctions, which substantially help increase safety. Katrakazas et al (2019) further explore these issues using a SSAM approach and find that this approach could be used in AVs to find dangerous road users and produce manoeuvres for other road users to avoid possible accidents. Table 1 reviews studies with a focus on the simulation of AVs and CAVs and the acquired methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Katrakazas et al. [38] constructed a joint risk assessment framework based on interactive perception motion model and dynamic Bayesian network (DBN).…”
Section: Safety Of Ivsmentioning
confidence: 99%
“…However, at present, the safety aspect of these automated driving has primarily been tackled with data and information gathered from in-vehicle sensors and equipment. Given the fact that a sensor failure is inevitable even with redundant measurements in a chain of operations, a holistic approach is required to guarantee a collision-free path planning of automated driving (Katrakazas et al, 2017). For example, a conflict detection technique may provide a critical hint of any collision-risk arising from the contextual and circumstantial factors such as collision hot-spots identified through historical collision data, unsafe traffic dynamics in real-time, infrastructure deficiencies, complex road layout, and other imminent threats from surrounding objects.…”
Section: Introductionmentioning
confidence: 99%